Efectos de algunas poliaminas en la protección contra las heladas y el grado de prolificidad en maíz (1990)
The treatments with polyamines reactivated the growth in plant heigth which had been interrupted by chilling. They also stimulated the development of a higher number of ear shoots (prolificity) and increased grain yield. The effects were specially observed in the MB 510 genotype.